2013
DOI: 10.4236/ojpm.2013.33040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics among Korean American male smokers between survey and cessation studies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This study employed a mixed-methods research design and is part of a larger telephone survey study conducted with a nationwide sample of Korean Americans. Findings pertaining to men were reported elsewhere [ 28 ]. Within the ethnic group, women were far less likely than men to disclose their smoking status, and, hence, we used multiple sampling strategies to recruit Korean American women.…”
Section: Methodsmentioning
confidence: 99%
“…This study employed a mixed-methods research design and is part of a larger telephone survey study conducted with a nationwide sample of Korean Americans. Findings pertaining to men were reported elsewhere [ 28 ]. Within the ethnic group, women were far less likely than men to disclose their smoking status, and, hence, we used multiple sampling strategies to recruit Korean American women.…”
Section: Methodsmentioning
confidence: 99%
“…Third, participants were treatment seeking individuals who may differ from the general population of Korean American smokers, which limits the generalizability of the findings. However, we found that participants in this study did not differ in terms of demographics and smoking behavior compared with a random sample of Korean American smokers who were not seeking treatment at the time [57]. …”
Section: Discussionmentioning
confidence: 99%